2512. The Trend in the Incidence of Herpes Zoster and Effect of Immune Status on Severity and Healthcare Utilization: Population-Based Study of Korea, 2003–2015. (26th November 2018) - Choi, Jae-Ki; Park, Sun Hee; Park, Sanghyun; Han, Kyung Do
Abstract: Background: An increase in the incidence of herpes zoster (HZ) is observed in South Korea. However, the effects of changes in population structure and immune status on the incidence and severity of HZ have not been well studied. We investigated longitudinal changes in the incidence of HZ and disease severity over time and according to age and comorbidities. Methods: We used population-based medical records from the National Health Insurance Service for approximately 50, 000, 000 subscribers from 2003 to 2015. Herpes zoster cases (period 2003–2015) or its complications (period 2007–2015) were identified using ICD-10 codes (B02-B02.9) and comorbid conditions were also collected. The annual crude incidence rates and age-standardized rates of HZ were calculated using direct standardization to the 2010 Korean Census population. Negative binomial regression was used to analyze the yearly incidence rate ratio (IRR) and the impact of immune status on disease severity. Healthcare utilization was compared across age groups and comorbid conditions. Results: The crude and age-sex standardized incidence rate of HZ annually increased over the study period (Figure 1). Such trend was also observed after adjusting for age, sex, immune status, and socioeconomic status (adjusted IRR 1.06, 95% CI 1.05–1.08). The incidence was highest in 61–80 year-olds whereas the relative increase was high in 11–30 year-olds (Figure 2). Incidences of HZ-associated hospitalizations and complications also steadily increased over time as well as across age groups (Figure 3) although the proportions among HZ cases remained stable. Among HZ cases, the risk of complications was higher among elderly population (71 years; IRR 1.1–1.23), patients with comorbidities (IRR 1.17, 95% CI 1.14-1.19), and male patients (IRR 1.19, 95% CI 1.09–1.38). The length of hospital stay (median 12 days [range: 7–25] vs. 8 days [range: 6–14], P < 0.001) was significantly greater in HZ patients with comorbidities than those without. Conclusion: The incidence of HZ has rapidly increased independent of population structure change. It is necessary to establish strategies such as vaccination to reduce the incidence of HZ, and efforts should be made to reduce the disease burden among those with comorbidities. Disclosures: All authors: No reported disclosures.